2019
DOI: 10.3389/fmats.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

High Figure-of-Merit Transparent Copper–Zinc Oxide Window Electrodes for Organic Photovoltaics

Abstract: We report a copper-zinc oxide bilayer electrode supported on flexible polyethylene terephthalate (PET) with a sheet resistance of 11. 3 sq −1 and average transparency of 84.6% in the wavelength range of 400-800 nm. The copper film is perforated with a dense array of sub-micron diameter apertures fabricated using polymer-blend lithography, which imparts broad band anti-reflectivity. We demonstrate proof-of-principle that it is possible to fabricate the polymer mask by dip coating which is a scalable deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[1] Due to the demand for miniaturization of integrated circuits to enable increased computing power, the dimensions of Cu interconnects in integrated circuits are now below 100 nm. [2] At the same time, nanostructured Cu is increasingly of interest for a wide range of emerging technologies, including next-generation photovoltaics, [3][4][5][6][7][8] lightemitting diodes, [9][10][11] sensors, [12][13][14] printed electronics, [15][16][17] high-frequency tags, [18,19] nano-generators, [20,21] and wearable electronics. [22][23][24][25] Cu is considered relatively stable toward oxidation in ambient air because, after the formation of the few nanometers of surface oxide (which occurs in the first few hours) the oxide layer thickness increases very slowly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Due to the demand for miniaturization of integrated circuits to enable increased computing power, the dimensions of Cu interconnects in integrated circuits are now below 100 nm. [2] At the same time, nanostructured Cu is increasingly of interest for a wide range of emerging technologies, including next-generation photovoltaics, [3][4][5][6][7][8] lightemitting diodes, [9][10][11] sensors, [12][13][14] printed electronics, [15][16][17] high-frequency tags, [18,19] nano-generators, [20,21] and wearable electronics. [22][23][24][25] Cu is considered relatively stable toward oxidation in ambient air because, after the formation of the few nanometers of surface oxide (which occurs in the first few hours) the oxide layer thickness increases very slowly.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] Cu films can be deposited by thermal evaporation in vacuum, which is a widely used deposition method compatible with roll-to-roll processing. [5,51] Thermally evaporated Cu films are polycrystalline with Cu (111), Cu (220), and Cu (222) being the dominant crystal faces at the surface. [52] Of these, it has been shown that the Cu (111) crystal face is the most resistant to oxidation due to high activation barriers to water dissociation to form copper hydroxide (which quickly reverts to CuO) and dissociative adsorption of O 2 , which leads to formation of Cu 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…To meet this new and exponentially-growing demand, the industry is seeking new flexible hybrid electronic solutions using printable circuits and components. Many of those key applications including solar cells 1 , 2 , light emitting devices 3 , haptic displays and touch screens 4 , wearable electronics 3 , 5 , 6 and biomedical sensors 7 usually require a high-performance transparent conductive electrode (TCE) technology compatible with high-speed manufacturing techniques and equipment. Ideally, a printable solution-based TCE solution would be compatible with traditional rigid substrates, but also with flexible substrates using polyethylene or polyimide, amongst others 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has a higher mobility and a spike rate similar to other materials (its low-field mobility reaches 14,000 cm 2 /V•s, the peak rate reaches 4.3 × 10 7 cm/s), and its electron transport rate is not affected by the temperature. Compared with extensive application of ZnO thin film materials (Lucarelli and Brown, 2019;Marikutsa et al, 2019;Pereira and Hatton, 2019;Qi et al, 2019Qi et al, , 2020aTharsika et al, 2019;Yu et al, 2019), all these properties endow InN unique advantages in the development and production of devices, such as highfrequency, high-speed transistors.…”
Section: Introductionmentioning
confidence: 99%